Proactive responses to the threats and opportunities of globalization (Philippines, 2004)
Trade liberalization is the progressive removal of all barries to trade. These barriers include tariffs, as well as non-tariff measures such as quantitative restrictions.
Keywords: Agriculturre,Nông nghiệp; Economic aspects,Khía cạnh kinh tế; South Vietnam,Đông Nam Á